THE PULSARS RADIO ILLUMINATION AND MAGNETIC MOMENTS OF NEUTRON STARS - Khachatrian, G. F. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
Using the formulas of the theory of radio emission of pulsars given in the review [1], based on the available observational data, the radiances of pulsars and the magnetic moments of 491 neutron stars were calculated.